Development of Domestic Chemical Industry in the Conditions of Globalization - Poliakova, Juliia; Shayda, Oksana; Novosad, Zoriana (Zeszyty Naukowe Wyższej Szkoły Bankowej w Poznaniu, 2024)
The article is devoted to the analysis of characteristic features, problems and prospects of development of the chemical industry of Ukraine in the conditions of action of global factors. The peculiarities of the functioning of the world market of the chemical industry are given. Based on the annual global rating “Global 500” and using the application package On Front, DEA-analysis was used to assess the effectiveness of the world’s leading chemical companies. Input variables — indicators of assets of companies and the number of their employees, and the output variable — an indicator of income, which allowed to determine the most optimal use of these enterprises resources that they direct to production activities. Attention is paid to find out of modern features and issues related to export activity of the domestic industry, which is formed under the influence of both internal transformations and global factors. The analysis of the industry development is conducted, a number of threats and challenges for its development are revealed. On the basis of the conducted research the perspective directions of further development of the domestic chemical branch are substantiated, which include the processes of import substitution, attraction of highly efficient investments, intensification of innovative activity, modernization of equipment, optimization of export and import structure. Keywords: chemical industry, exports, efficiency of activity, global economy, competitiveness of products